Recent changes in seasonal variations of climate within the range of northern caribou populations - Whitfield, Paul H.; Russell, Don (Rangifer, 2005)
The Arctic is one region where it is expected that the impacts of a globally changing climate will be readily observed. We present results that indicate that climate derivatives of potential significance to caribou changed during the past 50 years. Many temperature derivatives reflect the increasing overall temperature in the Arctic such as decreases in the number of days with low temperatures, increases in the number of days with thaw, and days with extremely warm temperatures. Other derivatives reflect changes in the precipitation regime such as days with heavy precipitation and number of days when rain fell on snow. Our results indicate that specific caribou herds from across the Arctic were subjected to different variations of these derivatives in different seasons in the recent past. Examination of temperature and precipitation at finer time-steps than annual or monthly means, shows that climatic variations in the region are neither consistent through the seasons nor across space. Decadal changes in seasonal patterns of temperature and precipitation are shown for selected herds. A process for assessing caribou-focused climate derivatives is proposed.